Q. 235.0( 1 Vote )
Mark the correct A. 0
For Identity element a * e = a = e * a, with ‘e’ being the identity element.
Given a * b =a + b - ab
⇒ a * e =a + e – ae
⇒ e(1-a) =0
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation